Identifikasi dan Pemetaan Lahan Kritis dengan Menggunakan Teknologi Sistem Infomasi Geografis : (Studi Kasus Kabupaten Bolaang Mongondow) - Doly H. Tiagas; Fabio W.M. Latuheru (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This study aims to identify and map critical land in Bolaang Mongodow Regency using Geographic Information System (GIS) technology. Critical land in question is an area that has experienced a decline in soil and environmental quality due to human activities. The methodology used includes collecting field data, processing data using GIS software, and analysis to produce a map of critical land. The results of this study are expected to provide useful information for land management and rehabilitation in the area.